Anakisis Penggunaan Metode STAD untuk Pembelajaran Matematika di MIS Yapis Al-Falah Bogor - Bahari, Ayu; Ernawati (Ikatan Dai Indonesia, 2022)
This study aims to analyze the effect of using the method on STAD (Student Teams Achievement Division) students' mathematics learning outcomes at MIS Yapis Al-Falah Bogor. This research is an experimental research method with the Student Teams Achievement Division (STAD) approach. STAD (Student Teams Achievement Division) The average pre-test score of mathematics before being taught using the STAD (Student Teams Achievement Division) method was 64 (low) at the MIS Yapis Al-Falah school. The results showed: the average post-test score of mathematics after being taught the STAD (Student Teams Achievement Division) method was 78 (high) at the MIS Yapis Al-Falah school. There is an effect of STAD (Student Teams Achievement Division) method on student learning outcomes with tcount = 7,897 and ttable = 2,14. It was concluded that the STAD method had a positive impact on the results of the fifth grade mathematics subjects at MIS Yapis Al-Falah Boogor.